A14 INFLAMMASOME ACTIVATION COORDINATES INTESTINAL MUCOSAL DEFENSE AGAINST THE ENTERIC BACTERIAL PATHOGEN SALMONELLA ENTERICA SEROVAR TYPHIMURIUM. (1st March 2018) - Crowley, S M; Graef, F A; Allaire, J M; Knodler, L A; Vallance, B
Abstract: Background: Intestinal epithelial cells (IECs) play a central role in the coordination of intestinal homeostasis. They must strike a careful balance to temper pro-inflammatory responses against the intestinal microbiota, while remaining vigilant and rapidly responsive when exposed to a noxious stimulus such as an enteric pathogen. One early response mechanism by which IECs engage in immune defense is through the activation of an IEC-specific inflammasome. This activation triggers the extrusion of infected IEC into the gut lumen, ultimately restricting Salmonella enterica serovar Typhimurium from escaping the gut and spreading systemically. However, it appears the role of the inflammasome in gut defense is not just restricted to IEC shedding but it also plays a key role in mucin secretion and antimicrobial lectin production. Aims: Here, we investigate the role of the inflammasome in mucosal defense against S. Typhimurium SL1344. Methods: This study employed a streptomycin pretreatment S. Typhimurium mouse infection model as well as various cell and immunofluorescent staining to characterize the role of the intestinal inflammasome. Results: Streptomycin-pretreated C57BL/6, Casp1/11 deficient (−/−) and Casp11−/− mice were orally infected and S. Typhimurium loads determined for each respective tissue at 18h and 72h post infection. Increased pathogen burdens were observed for both caspase-deficient mice compared to wild type, with increased systemic spread seen in the mesenteric lymph nodes, liver and spleen at both time points for Casp1/11−/− mice but only at 72h for Casp11 −/−. Interestingly, at 18h, despite increased bacterial loads, cecal pathology scores were decreased in both Casp1/11−/− and Casp11−/− mice, as compared to wild type. This was accompanied by increased intracellular S. Typhimurium immunofluorescence staining. Also, cecal mucin layer thickness, as measured by Alcian Blue as well as MUC2 immunofluorescence staining were similar amongst all mouse strains before infection, but were decreased in both Casp1/11−/− and Casp11−/− mice as compared to wild type after infection. Finally, expression of the antimicrobial lectins REG3γ and REG3β were significantly decreased in Casp11−/− mice as compared to wild type mice and minimal staining for REG3β was observed in both caspase deficient mice. Conclusions: These results indicate that the gut epithelium utilizes inflammasome signaling to coordinate multiple layers of innate defense at the gut mucosal surface to ultimately restrict enteric pathogen infections and systemic spread. Funding Agencies: CCC, CIHRNSERC, UBC